Edukasi pembuatan hand sanitizer berbahan alami kepada masyarakat di nagari persiapan aia manggih utara, Kecamatan Lubuk Sikaping - Hengki Firmanda; Gian Juliano (Unri Conference Series: Community Engagement, 2020)
This community empowerment activity in making hand sanitizers was carried out in the Nagari Persiapan Aia Manggih Utara, Kecamatan Lubuk Sikaping. WHO officially declared COVID-19 a pandemic due to the increasingly massive spread of COVID-19 in various countries. One of the efforts to avoid this virus is to maintain hand hygiene. Currently, many hand sanitizers are offered in the form of hand sanitizers because their use is more practical. Hand sanitizer is practical to use and can be carried anytime and anywhere. Generally, hand sanitzers are made using alcohol-based ingredients, but the use of alcohol on the skin is considered unsafe, besides that during the Covid-19 pandemic, hand sanitizers have become rare in the market. Therefore, one way to overcome this problem is to make a hand sanitizer made from natural ingredients from betel and lime leaves. The formulation of the problems that arise due to COVID-19 in the Nagari Persiapan Aia Manggih Utara, namely how to educate the public in making hand sanitizers made from natural ingredients, Techniques used in community empowerment related to the manufacture of hand sanitizers with natural ingredients are community participation, discussion and outreach. Based on the results of surveys and interviews conducted at the end of community service activities, 87% of the community understands how to make hand sanitizers made from natural ingredients, 95% of the community understands about COVID-19 and its symptoms of infection, 91% of the community understands efforts to prevent transmission of COVID-19, 88 % of people have understood the new normal policy (new normal habits), and 97% of people have experienced a decrease in income.